Border cinema : reimagining identity through aesthetics - Hanna, Monica; Sheehan, Rebecca, 1979- (New Brunswick, N.J. : Rutgers University Press, 2019)
The rise of digital media and globalization's intensification since the 1990s have significantly refigured global cinema's form and content. The coincidence of digitization and globalization has produced what this book helps to define and describe as a flourishing border cinema whose aesthetics reflect, construct, intervene in, denature, and reconfigure geopolitical borders. This collection demonstrates how border cinema resists contemporary border fortification processes. Showing how cinematic media have functioned technologically and aesthetically to engender contemporary shifts in national and individual identities, the contributors also propose alternative conceptions of these identities to those promulgated by the often restrictive current political rhetoric and ideologies that represent a backlash to globalization.
Frontmatter -- Contents -- 1. Introduction--Moving Images: Contesting Global Borders in the Digital Age / Hanna, Monica / Sheehan, Rebecca A. -- 2. Composite Aesthetics as Cultural Cartographies of Europe in Transition / Hassapopoulou, Marina -- 3. Undocumation: Documentary Animation's Unsettled Borders / Sheehan, Rebecca A. -- 4. The Art of Witness in Lourdes Portillo's Señorita extraviada / Fregoso, Rosa-Linda -- 5. The Cinematic Borderlands of Alejandro González Iñárritu's Babel / Hanna, Monica -- 6. Challenging European Borders: Goran Paskaljevic's Honeymoons / Pinzi, Anita -- 7. Remapping the Borderlands in ¿Quién diablos es Juliette? / Lahr-Vivaz, Elena -- 8. Crossing through el Hueco: The Visual Politics of Smuggling in Colombian Migration Films / Vargas, Jennifer Harford -- 9. Toward a Transfrontera-Latinx Aesthetics: An Interview with Filmmaker and Artist Alex Rivera / Aldama, Frederick Luis -- 10. No-Man's- Land: Shifting Borders and Alternating Identities in Contemporary Israeli Cinema / Zanger, Anat / Gertz, Nurith -- 11. The Borders We Cross in Search of a Better World: On Border Crossing in Three of Amos Gitai's Feature Films / Munk, Yael -- 12. Filipinos at the Border: Migrant Workers in Transnational Philippine Cinema / Capino, José B. -- Acknowledgments -- Bibliography -- Filmography and Videography -- Notes on Contributors -- Index
Includes bibliographical references (pages 219-229), filmography (pages 231-232) and index.
eBooks on EBSCOhost
Keywords: Boundaries in motion pictures; Identity (Psychology) in motion pictures; Motion pictures -- Aesthetics; Digital cinematography; Frontières au cinéma.; Identité (Psychologie) au cinéma.; Cinéma -- Esthétique.; Cinéma numérique.; PERFORMING ARTS -- General; Boundaries in motion pictures; Digital cinematography; Identity (Psychology) in motion pictures; Motion pictures -- Aesthetics; Film; Grenze; Globalisierung; Identität; media, digital media, borders, global, globalization, digital, cinema, geopolitical, regional border, global cinema